(untitled) (Vietnam Journal of Community Medicine, 2021)
A descriptive regression study evaluating surgical outcomes of 67 patients diagnosed with benign adrenal tumors and treated with retroperitoneal laparoscopic surgery at Viet Duc Hospital in 2018. Results: For Surgical subjects mainly belonged to ASA group I or II, the average surgery time of the study subjects was 71.04 ± 23.50. In the group of pathological tumors, the surgical time of the group of patients with non-secretory tumours was the longest (74.2 ± 23.2 minutes); The operative time of the group of patients with Conn’s disease was the shortest (67.5 ± 26.1 minutes). The average operating time of the group of tumors from 1-10mm in size was 60 minutes. 66/67 patients with total thoracic resection due to tumor accounted for 98.5%. Only 1/67 patients with selective resection of TTT. Out of a total of 67 patients studied, there were 2 patients with subcutaneous emphysema, accounting for 3.0%.